PHASE TRANSFORMATIONS IN STEELS UNDER CONTROLLED QUENCHING IN A MAGNETIC FLUID - Alexander Yakovlevich Simonovsky (Наука. Инновации. Технологии)
Introduction: In this paper we study structures and related mechanical properties of a number of tool steels subjected to quenching cooling in a magnetic fluid with different contents of the magnetic phase under the action of a constant magnetic field of different intensity. The possibility of controlled quenching in a magnetic luid is determined by the dependence of the cooling intensity on the luid composition, the magnitude and degree of inhomogeneity of the magnetic ield created near the cooled surface. The different intensity of cooling causes different mechanisms of phase transformations in steel during the quenching process. Materials and methods: when choosing the object of research - samples of tool steels - proceeded from the regularities of phase transformations occurring in steels with different cooling intensities. The goal was achieved by the choice of steel grades characterized by varying degrees of stability of the supercooled austenite and, thus, a different value of the critical quenching rate, the cooling rate, which ensures only the diffusionless mechanism of austenite transformation. Results of the study: for the irst time it was found that by changing the intensity of the magnetic ield during quenching in samples of small sizes of steels with lowered stability of supercooled austenite, their hardness can be controlled. Discussion and conclusions: the results of the research made it possible to identify a new promising direction when using a magnetic luid as a quenching medium - performing hardening cooling.